The groove configuration of mandibular molars of Malaysians of Mongoloid ancestry - Calvin Jia Jun; Yeoh Sharlini Bee Ying; Nur Nabila Hayati Shushilil Azam; Prathap Chander Manivannan; Wong Gou Rean; Phrabhakaran Nambiar (Universidad de Concepción., 2023)
Aim: Variation in dental structures is widely accepted as a combination of multiple factors such as gender, environmental effects and genetics. However, the characterization of similarities and differences in dental morphology has been lacking in relation to the factors mentioned. This study aims to assess and compare the variations in traits in mandibular molars and the influence of gender and ethnicity in affecting these traits amongst the Malaysian population of Mongoloid ancestry. Materials and Methods: Our study population was 180 dental casts of patients, from 15 to 40 years old, comprising 56 Malays and 124 Chinese; 60 were males and 120 were females. Traits like groove pattern, number of cusps, protostylids and deflecting wrinkles were observed, scored, and recorded. Results: This study revealed that the most common mandibular first molar (M1) was characterized by 5 cusps and displayed 'Y' groove pattern, while the most common mandibular second molar (M2) had 4 cusps and exhibited a groove pattern that resembled a '+'. Notably, all the traits studied were bilaterally symmetrical, except for the groove pattern of M1, while sexual dimorphism was observed in groove patterns of M2. Conclusions: This study found that M1 had a preponderance of 5 cusps with 'Y' groove pattern, while M2 were typically 4-cusped with '+' groove pattern.